Successful term pregnancy after uterine artery embolization for caesarean scar ectopic pregnancy: a case report - Job, Angeline; S., Spandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
The incidence of caesarean scar pregnancy range from 1 in 1800 to 1 in 2500 of all pregnancies. It has been estimated that 6.1% of pregnancies in women with at least one previous Caesarean section and a diagnosis of ectopic pregnancy will be Caesarean scar pregnancy (CSP). There is no consensus on the management of CSP. An invasive intervention such as excision of scar ectopic can reduce recurrence but affects patient’s fertility. Conservative management like administration of methotrexate and uterine artery embolization (UAE) is specially important for young women who want to keep their fertility. This is a case report of a 29-year-old woman who presented with persistent heavy bleeding following failed MTP at 12 weeks of gestation. Ultrasonogarphy was suggestive of Caesarean scar pregnancy and MRI of chronic left adnexal ectopic. Laparotomy also was suggestive of Caesarean scar ectopic. She was managed conservatively with UAE followed by Methotrexate. The procedure was performed successfully, and the patient’s fertility was preserved. Follow up consisted of serial bhCG monitoring which gradually returned to normal levels. She conceived four years after UAE and had an uneventful antenatal period and underwent Elective Cesaraen section at 38 weeks. For those patients with CSP who desire future pregnancy, the comprehensive treatment including UAE can be considered in management.